2016
DOI: 10.1103/physrevlett.116.124501
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Uniform Coating from the Interplay of Marangoni Flows and Surface-Adsorbed Macromolecules

Abstract: Surface coatings and patterning technologies are essential for various physicochemical applications. In this Letter, we describe key parameters to achieve uniform particle coatings from binary solutions: First, multiple sequential Marangoni flows, set by solute and surfactant simultaneously, prevent non-uniform particle distributions and continuously mix suspended materials during droplet evaporation. Second, we show the importance of particle-surface interactions that can be established by surface-adsorbed ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
297
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(306 citation statements)
references
References 47 publications
5
297
3
1
Order By: Relevance
“…In the final stage, the outward flow was identical to that found in pure water drops. Qualitatively similar continuous mixing by distinct Marangoni flows has been recently observed in evaporating drops of whiskey15. It should be noted that the evaporation of the binary-mixture drops features a solutal-thermocapillary flow, that is, σ = σ 0 − γ T ( T − T 0 )− γ c ( c − c 0 ) where γ T =−∂ σ /∂ T , γ c =−∂ σ /∂ c , and c here is the ethanol concentration in the liquid; normally, .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In the final stage, the outward flow was identical to that found in pure water drops. Qualitatively similar continuous mixing by distinct Marangoni flows has been recently observed in evaporating drops of whiskey15. It should be noted that the evaporation of the binary-mixture drops features a solutal-thermocapillary flow, that is, σ = σ 0 − γ T ( T − T 0 )− γ c ( c − c 0 ) where γ T =−∂ σ /∂ T , γ c =−∂ σ /∂ c , and c here is the ethanol concentration in the liquid; normally, .…”
Section: Resultssupporting
confidence: 73%
“…This is in an effort to ameliorate the complexity of the evaporation process related to a delicate interaction between the bulk flow45678, evaporation kinetics91011, thermocapillary stability1213 and binary-mixture dynamics141516. The flow is complicated further by the presence of moving contact lines as well as regions of high curvature, both of which influence the evaporation.…”
mentioning
confidence: 99%
“…On the other hand, in some cases, the whole solid is deposited near the center of the drop [13,23,109]. This is more prominent when the angle of contact is large and is named the Marangoni effect [54,[110][111][112]. It arises due to a gradient in surface tension.…”
Section: Evaporation Of a Suspension Of Micro-or Nanoparticlesmentioning
confidence: 99%
“…Recently, Kim et al . 18 reported that multiple sequential Marangoni flows and particle-surface interactions are key parameters to achieve uniform particle coatings in a droplet and suggested a small concentration of surfactant and surface-adsorbed polymer via physisorption for a uniform deposit in a binary mixture.…”
Section: Introductionmentioning
confidence: 99%